Urban Dynamics and Vulnerability to Disasters in Lagos State, Nigeria (1982 – 2012) (2014)
The terrain, morphology, socio-economic characteristics coupled with lateral urban growth and increasing population concentration expose Lagos state to different types of disaster. Studies on disasters in Lagos have focused on the types and their impact to the neglect of vulnerability factors and disaster patterns. This study, therefore, investigated the relationship between urban dynamics (change in population, morphology and urban spatial expansion) and vulnerability to disasters in Lagos state (1982-2012) where flooding and building collapse are common occurrences. Forrester‟s urban dynamics theory provided the analytical framework. Cross-sectional survey design was adopted. A multi-stage sampling technique was used to select 1576 Heads of Household (HH) in direct proportion to existing housing stock in five Mainland Local Government Areas (LGAs) [Lagos Mainland –LM (67), Mushin (153), Oshodi-Isolo (197), Shomolu (214) and Surulere (106] and four Lagos Suburb (LS) LGAs [Alimosho (290), Ajeromi-Ifelodun (232), Ikorodu (234) and Kosofe (83]. A structured questionnaire was used to collect data from HH. Observation checklist containing vulnerability indices and satellite imagery were used to document existing infrastructural facilities and residential neighbourhood densities, adherence to urban and regional planning regulation and standards in addition to recorded data on building collapse in Lagos state. The National Population Commission‟s trend of population growth in LM and LS and Land Use/Land-cover Change (LULC) imageries obtained from Global Land Cover Facility were used as urban dynamics indices. Geographic Information System was used to analyse LULC (Landsat imageries 1984 and 2010) and to simulate flood-risk scenarios. Data were analysed using descriptive statistics, logistic regression and ANOVA at p≤0.05. Eighty-eight per cent of the buildings were built of sandcrete blocks (91.4% in LS and 83.9% in LM); 84.2% (LS) and 38.3% (LM) were not linked to pipe-borne water, while, 72.3 % (LS) and 43.1% (LM) did not have storm water drainage. About 74.0% (LS); 37.2% (LM) did not adhere to planning setback and maximum building-plot ratio. Also, 68.0% (LS) and 27.3% (LM) had encroached into natural flood plains. One hundred and thirty-eight buildings collapsed in the study area with 81.9% occurring in LM. Population of LM increased by 32.3% while that of LS increased by 87.4%. Vegetation cover reduced from 46.5% to 26.6% in LS and from 32.7% to 22.3% in LM while urban land use increased from 17.3% to 51.3% in LS and from 28.8% to 31.5% in LM. Buildings became vulnerable as flood-risk increased by one metre Above Sea Level (ASL) (8.3% in LM; 17.6% in LS). At two metres ASL, (19.1% LM; 31.5% LS) buildings were vulnerable to flood. The effects of urban dynamics on vulnerability to flood (R2=0.473) and building collapse (R2=0.524) were significant. Vulnerability to disaster varied by housing density across residential neighbourhoods for building collapse (F(2,86)=17.88). Increasing population growth, flood-plains encroachment and non-adherence to planning regulation are factors influenced vulnerability to disaster in Lagos state. Adherence to land use planning regulation and flood-plain buy-back were recommended as vulnerability reduction strategies.